The absorption spectrum of water vapor in the 2.2 μm transparency window: High sensitivity measurements and spectroscopic database; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 189 - Campargue A. Alain; Mikhailenko S. N. Semen Nikolaevich; Vasilchenko S. S. Semen Sergeevich; Reynaud C.; Beguier C. Serge; Cermak P. Peter; Mondelain D.; Kassi S. Samir; Romanini D. Daniele (2017, 2017)
Title screen